SAFE ZONE OF JOINT LINE ELEVATION FOR THE TREATMENT OF KNEE FLEXION CONTRACTURE PREVENTING MID-FLEXION INSTABILITY IN TOTAL KNEE REPLACEMENT - Nauman Abbas; Khattak, Sabir Khan; Muhammad Umer Faheem; Naeem Ahmed; Amer Aziz; Latif Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: In osteoarthritic knee, flexion deformity is caused by synovial inflammation, posterior femoral and tibial osteophytes tenting onto the capsule, ligamentous contracture and hamstring shortening. This study aimed to evaluate the safe zone of joint line elevation for the treatment of flexion knee contracture preventing mid-flexion instability in total knee replacement. Methods 51 knees with varus osteoarthritis undergoing TKA were evaluated. 39 knees with flexion contracture < 15°and 12 knees with flexion contracture >15°. 2-mm joint line elevation was performed in just 4 knees with >15° flexion contracture. The extension and flexion gaps were measured with traditional spacer block. Stability in coronal plane (varus & valgus stress) was assessed at 0,30,60 & 90 degrees. Sampling Technique was non probability consecutive. SPSS 23 was used for statistical analysis. Results: The study comprises 51 patients undergoing total knee replacement (TKA) for osteoarthritis, with a notable gender distribution (84.3% women, 15.7% men) and a mean age of 60.24±8.54 years. Of these, 41.2% had both knees affected, and joint elevation was performed in 23.5% with flexion contracture >15°. No instability was found in cases with joint line elevation. Flexion contracture analysis revealed asymmetry across sides, yet no statistically significant differences. Detailed comparisons show variability in flexion contracture and range of motion, emphasizing the complexity of side-specific outcomes. The study underscores the importance of tailored evaluation and intervention for flexion contracture >15° to optimize postoperative results. Conclusions This study has shown that in patients with varus osteoarthritis of the knee and flexion contracture > 15°, a 2-mm joint line elevation is safe to treat knee flexion contracture and is not associated with mid-flexion laxity. Level of evidence IV Cross sectional study.